The talking dead in Late Bronze Age Dendra: storytelling, outreach and public engagement - Sampatakou, Despoina Vasiliki (2018)
This thesis aims to explore whether storytelling is an appropriate tool for disseminating archaeology in schools and the wider public in Greece. The main objectives are to study how archaeological narratives may address educational needs, identify the benefits of archaeological storytelling for schoolchildren, and discuss the limitations and the challenges of the creation of such narratives. The theoretical framework for this study is based on the main principles of Public Archaeology, the Archaeology of Personhood and the Archaeology of Emotions. The research conducted is qualitative and indicative, studying primary and secondary data including archaeological reports, iconographical data, Linear B records and the Homeric Epics, and the scholarship available from the fields of Public Archaeology, the Archaeology of Personhood and the Archaeology of Emotions. In order to achieve the aims and objectives of this thesis, I have chosen to create two archaeological narratives based on the Tholos tomb and the so-called ‘Cenotaph’ from the Mycenaean cemetery at Dendra in the Argolid, Greece. The analysis focuses on how archaeological storytelling can be an appropriate and valid way of discussing Mycenaean burial customs and the emotions related to death in a Greek classroom.